Pelatihan Optimalisasi Pemanfaatan AI Berbasis Scite.Ai Untuk Penulisan Literatur Review - Nurfaika, Nurfaika; Pratama, M. Iqbal Liayong (Universitas Negeri Gorontalo, 2026)
This community service activity aimed to enhance the competencies of Master’s students in Geography Education at the Graduate School of Universitas Negeri Gorontalo (UNG) in optimizing the use of Artificial Intelligence (AI), particularly Scite.ai, for literature review writing. The main issue identified was the participants’ limited understanding of AI-based tools for reference searching and systematic, evidence-based literature synthesis. The program employed a participatory hands-on training approach involving six active graduate students and was conducted at the Graduate Lecture Building of UNG. Evaluation was carried out using pre-test and post-test assessments to measure competency improvement. The pre-test results indicated that 0% of participants understood how to use Scite.ai for contextual citation analysis. After the training and practical sessions, post-test results demonstrated that 100% of participants were able to independently use the application and successfully produce a complete Chapter II (Literature Review) draft aligned with their respective thesis topics. The activity proved effective in improving AI literacy, contextual citation analysis skills (supporting, contrasting, mentioning), and the overall quality of academic argumentation. Continuous implementation of similar training programs is recommended to support research quality enhancement and scholarly publication in higher education institutions.